Culture as a factor of interest for learning French as a foreign language - Delgado Rocha, Jorge Gustavo (2020)
This article presents the French culture and its role as a decision factor for the students of the French Alliance of Quito (AFQ) to choose the French language for learning a foreign language and above all to complete their studies. For this, the culture has been determined from its social definition and the different ways of presenting it to the target audience, in the same way the object of study has been chosen, because the French Alliance is a reference in the education of the French language as foreign language in Ecuador. A qualitative and quantitative analysis was made to observe the importance that the students and board of the Alianza Francesa de Quito give to the promulgation of culture inside and outside the classroom. The research is aimed at determining the image of the institution that has been generated together with the use of the French-speaking culture within the target audience studied, that is, students of the French Alliance of Quito. In this way, it is intended to determine the level of influence of culture for the learning of French within the institution, together with the different cultural activities and events that take place in the French Alliance of Quito.